ANALYSIS OF ECONOMIC VALUE OF THE CONTINGENT VALUATION METHOD APPROACH IN TABLOLONG BEACH TOURISM, WEST KUPANG DISTRICT, KUPANG REGENCY - Hapsa Usman; Siti Mujanah; Abdul Halik (RADJA PUBLIKA, 2025)
Tourism in East Nusa Tenggara is still very natural, there are many natural tourist destinations that can provide nuances of beauty and coolness. One of them is Tablolong Beach which is located in Tablolong Village, West Kupang District, Kupang Regency. This beach is very large and is never quiet and visited by tourists who come from various regions. Tablolong Beach has a fairly calm wave with a stretch of white sand mixed with soft chocolate. The condition of the sand is quite wide and sloping, so it allows you to do various exciting activities. In addition to being a recreational event, tablolong beach is known as a fishing tourism village because the coast is open sea and has abundant marine potential, so it is not surprising that many visitors every week visit and fish on this beach, but since the covid19 pandemic the condition of this tourist beach has begun to become quiet, this has given the economic effect of tourism to decrease. This research was conducted at the Tablolong Beach tourist attraction located in West Kupang District, Kupang Regency. This study aims firstly to analyze visitor assessments of Tablolong Beach tourist destinations and where visitors come, second to analyze the economic value of Tablolong Beach Ecotourism with the Contingent Valuation Method approach. The sampling technique used in this study uses Accidental Sampling. The analysis method used in this study is a quantitative descriptive research using the Contingent Valuation method. The results of this study concluded that the general assessment of visitors towards Tablolong Beach Ecotourism tourism was quite good. With the highest percentage of visitor answers of 65.80%. The majority of visitors as many as 62% come from the Kupang City area and as many as 38% come from outside Kupang City. The economic value of Tablolong Beach Ecotourism tourism with the Contingent Assessment Method approach, which can be known from the total income of the visitor's Willingness to Pay (WTP) is Rp. 2.230.203.600 per month. The number will increase on holidays and days where there are activities or events.